PEMANFAATAN SARI KULIT PISANG KEPOK (Musa paradisiaca L.) SEBAGAI MINUMAN FERMENTASI MENGGUNAKAN Lactobacillus plantarum B1765 - Annisa Suci Hermansyah; Prima Retno Wikandari (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
Kepok banana peel is an agricultural waste that has not been optimally utilised. Efforts are needed to utilise the waste that provides added value as a food product. Fermented beverage is one of the products that can be developed based on the nutritional potential of kepok banana peel. This study was conducted to determine the effect of variation in fermentation duration on product quality including microbiological quality (Total Lactic Acid Bacteria (LAB)), chemical quality (pH and Total Titratable Acid (TAT)) and organoleptic quality (Colour, Taste and Aroma) in kepok banana peel fermented beverage using Lactobacillus plantarum B1765. Fermentation was carried out for 0, 6, 12, 18, 24 and 30 hours at 37°C. Total LAB was calculated using the Total Plate Count (TPC) method, pH was determined using a pH meter, and TAT was tested using the acid-base titration method. Meanwhile, organoleptic was tested using the panellist's favourite level quality test. The results showed that the fermentation time reached the highest LAB growth up to 2.23 x 108 CFU/mL at 12 hours fermentation. pH decreased from 6.07 to 3.82 and TAT increased from 0.14% to 0.7% at 30 hours fermentation. Meanwhile, the level of panellists' liking reached an optimum at 24 hours with the category of liking. According to SNI 7552:2018 from the aspects of total LAB, TAT, and organoleptic, the best fermentation time is 24 hours.